Pressureless sintering silicon carbide ceramic convenient to process and preparation method thereof

By adopting specific formulas and processes, including the combination of α-SiC ultrafine powder, β-SiC ultrafine powder, boron carbide micro powder, carbon fiber and carbon nanotubes, as well as high-speed grinding and isostatic molding, the problem of insufficient strength and toughness in the processing process of pressure-free sintered silicon carbide ceramics is solved, and efficient and precise processing effects are achieved.

CN119874375AActive Publication Date: 2025-04-25ZIBO GT INDAL CERAMICS
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510368434.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-27
Publication Date
2025-04-25
Estimated Expiration
2045-03-27

AI Technical Summary

Technical Problem

During the processing process, existing pressureless sintered silicon carbide ceramics have problems such as low green strength, poor toughness, long processing time and low yield. The existing processes are prone to abnormal growth of grains, residual additives, and easy collapse of workpieces.

Method used

The formula containing α-SiC ultrafine powder, β-SiC ultrafine powder, boron carbide micro powder, carbon fiber and carbon nanotubes was adopted, and the network structure was formed by high-speed grinding of stirring mill. Combined with isostatic molding and vacuum sintering processes, pressure-free sintered silicon carbide ceramics with high strength and high toughness were prepared.

Benefits of technology

It improves the green strength of pressureless sintered silicon carbide ceramics and the toughness of the products after sintering, reduces processing time and defect rate, and improves the processing accuracy and efficiency of the finished product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses pressureless sintered silicon carbide ceramic convenient to process and a preparation method thereof, and relates to the technical field of ceramic. The total mass of the components except the binder, the dispersing agent, the plasticizer, the lubricant and the water is 100%; the binder, the dispersing agent, the plasticizer, the lubricant and the water account for the total mass percentage of the other components: 91-95% of alpha-SiC superfine powder, 3-5% of beta-SiC superfine powder, 0.5-1% of boron carbide superfine powder, 0.5-2.5% of carbon fibers, 0.5-2.5% of carbon nanotubes, 6-9% of binder water-soluble phenolic resin, 0.5-1.5% of the dispersing agent, 1-3% of the plasticizer consisting of polyvinyl alcohol and carboxymethyl cellulose in a mass ratio of 1: 1, 1-3% of the lubricant and 100% of the water; the total mass of the binder and the plasticizer is 7-10%, and the mass ratio of the binder to the plasticizer is 18: (2-9). The machining precision and machining efficiency of products can be improved, and machining defects are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramics, and in particular to pressureless sintered silicon carbide ceramics which are easy to process and a preparation method thereof. Background Art

[0002] The outstanding features of pressureless sintered silicon carbide ceramics are superhardness and wear resistance (Mohs hardness reaches 9-9.5, close to diamond), high temperature stability (maintaining stable performance at high temperatures of 1600°C), chemical corrosion resistance (strong resistance to corrosive media such as acids, alkalis, and molten metals), and good thermal shock resistance (low thermal expansion coefficient and can withstand rapid temperature changes).

[0003] Pressureless sintered silicon carbide ceramics have a wide range of applications, mainly in industrial manufacturing (cutting tools, wear-resistant liners, seals), electronics and semiconductors (high-temperature radiators, insulators, precision stages for photolithography machines, energy storage battery module substrates), national defense and security (bulletproof armor, aerospace high-temperature components), new energy and environmental protection (furnace linings, crucibles, heat exchangers) and other fields.

[0004] However, the superhardness of pressureless sintered silicon carbide ceramics makes it difficult to process, takes a long time to process, and has a low yield rate. The formed green body is very brittle, and the processing process can easily cause the edges and corners of the workpiece to collapse, making it difficult to pre-process. At the same time, the solid-phase sintering used in the existing technology can easily lead to abnormal grain growth (grains>10μm), reducing the fracture toughness of the product (about 3.5MPa·m¹ / ²); the residual binding phase (such as Al2O3-Y2O3 system) from liquid phase sintering weakens the grain boundary bonding and affects the overall strength of the material. The additives and silicon carbide powder are mixed unevenly to form an additive-rich area, resulting in uneven distribution of the liquid phase, affecting the densification effect. Although hot pressing sintering can improve the density of the product (>99%), it requires high-pressure equipment and is costly, making it difficult to apply on a large scale. Obviously, the coarse grains, residual additives and process limitations of the product are still the core bottlenecks that restrict its toughness improvement.

[0005] Chinese invention patent CN102537510B discloses a preparation process for pressureless sintered silicon carbide ceramic valve cores, the raw materials are as follows: 80-100 parts by weight of silicon carbide, 0.1-1 parts of boron carbide powder with a particle size of less than 200 mesh, 0.5-3 parts of polyvinyl alcohol, an appropriate amount of dispersant, and 0.1-1 parts of water-soluble polyethylene oxide resin, after raw material configuration, spray granulation, mold loading, pressure forming, drying, rough processing, high temperature sintering, and fine processing to size, the finished valve core and valve seat are obtained. However, the single binder added in this preparation process is relatively small, and the strength and toughness of the green body formed after molding are low. Pre-processing in advance will cause the green body to have broken edges and corners.

[0006] Chinese invention patent CN105198434A discloses a high-performance pressureless sintered silicon carbide bulletproof ceramic and its preparation method, the components and weight ratio of which are: 96-99 parts of silicon carbide ultrafine powder, 1-2 parts of boron carbide ultrafine powder, 0.2-1 parts of nano-titanium boride, 10-20 parts of water-soluble phenolic resin, and 0.-0.5 parts of high-efficiency dispersant. After ball milling, spray granulation, dry pressing, green body curing, and vacuum sintering, the final product is obtained. This patent uses a large amount of water-soluble phenolic resin and excessive organic binder in the production process, which will cause the slurry to have too high a consistency, uneven distribution of various raw materials during the homogenization process, and agglomeration of the slurry, resulting in defects in the green body after molding, reducing the strength and toughness of the material, and defects are also prone to occur in the green body processing process.

[0007] In summary, it is necessary to develop a new pressureless sintered silicon carbide ceramic and its preparation method to solve the above problems. Summary of the invention

[0008] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a pressureless sintered silicon carbide ceramic that is easy to process and a preparation method thereof, which not only improves the strength of the pressureless sintered silicon carbide ceramic green body, but also improves the toughness of the sintered product. The green body can be pre-processed in advance according to the size requirements of the product to avoid damage, and in the subsequent fine processing, simple grinding is required to achieve the product size, which is beneficial to improving the processing accuracy and processing efficiency of the product and reducing processing defects.

[0009] The technical solution of the present invention is: On the one hand, the present invention provides a pressureless sintered silicon carbide ceramic that is easy to process, comprising the following components in percentage by mass, wherein the total mass of the remaining components except a binder, a dispersant, a plasticizer, a lubricant, and water is calculated as 100%, and the binder, the dispersant, the plasticizer, the lubricant, and the water are calculated as a percentage of the total mass of the remaining components: 91-95% of α-SiC ultrafine powder, 3-5% of β-SiC ultrafine powder, 0.5-1% of boron carbide powder, 0.5-2.5% of carbon fiber, 0.5-2.5% of carbon nanotubes, 6-9% of binder, 0.5-1.5% of dispersant, 1-3% of plasticizer, 1-3% of lubricant, and 100% of water; the total mass of the binder and the plasticizer is 7-10%, and the mass ratio of the binder to the plasticizer is 18:(2-9); wherein the binder is a water-soluble phenolic resin, and the plasticizer is polyvinyl alcohol (PVA) and carboxymethyl cellulose (CMC) in a mass ratio of 1:1.

[0010] Preferably, the purity of the α-SiC ultrafine powder is greater than 99.5wt.%, and the median diameter is 0.5-0.7μm.

[0011] Preferably, the purity of the β-SiC ultrafine powder is greater than 99.5wt.%, and the median diameter is 0.1-0.2μm.

[0012] Preferably, the purity of the boron carbide powder is greater than 99wt.%, and the median diameter is 0.5-1μm; the purity of the carbon fiber is greater than or equal to 98wt.%, and the diameter is 50-200nm, and the length is 5-7μm; the purity of the carbon nanotube is greater than or equal to 98wt.%, and the diameter is 10-25nm, and the length is 0.5-0.6μm.

[0013] Preferably, the dispersant is ammonium polyacrylate.

[0014] Preferably, the lubricant is oleic acid.

[0015] On the other hand, the present invention provides a method for preparing the pressureless sintered silicon carbide ceramic that is easy to process, comprising the following steps: S1 Ingredient grinding: add water, binder, dispersant, plasticizer, lubricant into a stirred mill for grinding, then add boron carbide powder, carbon fiber, carbon nanotubes for grinding, and finally add α-SiC ultrafine powder and β-SiC ultrafine powder for grinding; S2 uses a screen to screen the mud ground in step S1; S3 granulating the slurry screened in step S2 to obtain granular material; S4 sieving the granular material to obtain granulated powder; S5 isostatically pressing the granulated powder to obtain a green body; S6 drying the green body; S7 performs pre-processing on the green body after drying; S8 sintering the pre-processed green body to obtain pressureless sintered silicon carbide ceramics that are easy to process.

[0016] Preferably, in step S5, the isostatic pressing pressure is 150-200 MPa.

[0017] Preferably, in step S6, the drying temperature is 120-180° C. and the drying time is 6-12 hours.

[0018] Preferably, in step S8, the sintering process is: at a vacuum degree of 10 -2 Pa, the temperature is raised from room temperature to 600-800°C at a rate of 20-40°C / h and kept for 4-8h, then argon is introduced to raise the temperature to 2100-2250°C at a rate of 10-30°C / h and kept for 1-3h, and the temperature is naturally lowered to obtain pressureless sintered silicon carbide ceramics that are easy to process.

[0019] Compared with the prior art, the present invention has the following beneficial effects: 1. The pressureless sintered silicon carbide ceramics prepared by the present invention have high green strength and high green body density after sintering (bulk density ≥3.13g / cm3 ), and has high fracture toughness (fracture toughness ≥5.6MPa·m 1 / 2 ), which greatly reduces the pre-processing time of the green body, and reduces the complex processing procedures of the sintered product and the edge and corner collapse during the processing. The finished product rate after sintering and fine processing is ≥95%, which significantly improves the processing efficiency and product qualification rate.

[0020] 2. The present invention adds water-soluble phenolic resin, polyvinyl alcohol and carboxymethyl cellulose, which are fully dispersed through high-speed grinding in a stirred mill to form a network structure, thereby enhancing the binding force between powder particles, improving the molding performance and initial strength of the green body after molding, and providing basic conditions for the feasibility of green body processing.

[0021] 3. The present invention adds nano cubic β-SiC ultrafine powder, so that α-SiC (high temperature stable) ultrafine powder and β-SiC (low temperature stable) ultrafine powder can form a grain boundary strengthening effect, and the fine grains (nanoscale) of the β-SiC ultrafine powder can be used as sintering active sites to promote the diffusion reaction between the α-SiC ultrafine powder particles; at the same time, the high temperature stable α-SiC ultrafine powder can inhibit the abnormal growth of grains, so that the sintered body maintains a fine grain structure, thereby improving the strength and toughness, reducing the complex processing procedures of the sintered product, and only fine processing is required.

[0022] 4. The present invention adds a composition of boron carbide powder, carbon fiber and carbon nanotubes, which improves toughness by bridging cracks and dispersing stress, thereby playing the role of a toughening agent. DETAILED DESCRIPTION

[0023] In order to enable persons skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.

[0024] Example 1 The formula of the pressureless sintered silicon carbide ceramic that is easy to process in this embodiment is shown in Table 1, and the preparation method includes the following steps: S1 Ingredient grinding: add water, binder, dispersant, plasticizer and lubricant into a stirred mill and grind for 1 hour, then add boron carbide powder, carbon fiber and carbon nanotubes and grind for 1 hour, finally add α-SiC ultrafine powder and β-SiC ultrafine powder and grind for 2 hours; S2. Screen the mud ground in step S1 using a 180-mesh screen to remove lumps in the mud; S3: pouring the slurry screened in step S2 into a mixing barrel and starting granulation to obtain granular material; S4 sieve the granular material to 80 mesh to remove large particles to obtain homogenized granulated powder; S5: pouring the granulated powder into a mold for isostatic pressing at a molding pressure of 150 MPa to obtain a green body; S6: keeping the green body at 120°C for 8 hours for drying; S7 pre-processes the dried green body according to the designed shape and size; S8 The pre-processed green body is placed in a vacuum furnace and protected by a sagger for sintering: vacuum is drawn to 10 -2 Pa, heating to 800℃ at a rate of 20℃ / h and keeping it for 4h for degreasing, then introducing argon gas and heating to 2100℃ at a rate of 30℃ / h and keeping it for 3h, and cooling naturally to obtain pressureless sintered silicon carbide ceramics that are easy to process; S9 finishes the pressureless sintered silicon carbide ceramics to obtain the required product parts. During the processing, the pressureless sintered silicon carbide ceramics will not break or fall off.

[0025] Example 2 The formula of the pressureless sintered silicon carbide ceramic that is easy to process in this embodiment is shown in Table 1, and the preparation method includes the following steps: S1 Ingredient grinding: add water, binder, dispersant, plasticizer and lubricant into a stirred mill and grind for 1 hour, then add boron carbide powder, carbon fiber and carbon nanotubes and grind for 1 hour, finally add α-SiC ultrafine powder and β-SiC ultrafine powder and grind for 2 hours; S2. Screen the mud ground in step S1 using a 180-mesh screen to remove lumps in the mud; S3: pouring the slurry screened in step S2 into a mixing barrel, and starting granulation to obtain granular material; S4 sieve the granular material to 80 mesh to remove large particles to obtain homogenized granulated powder; S5: pouring the granulated powder into a mold for isostatic pressing at a molding pressure of 180 MPa to obtain a green body; S6: keeping the green body at 150°C for 12 hours for drying; S7 pre-processes the dried green body according to the designed shape and size; S8 The pre-processed green body is placed in a vacuum furnace and protected by a sagger for sintering: vacuum is drawn to 10 -2 Pa, heating to 700℃ at a rate of 30℃ / h and keeping it for 6h for degreasing, then introducing argon gas and heating to 2150℃ at a rate of 20℃ / h and keeping it for 2h, and cooling naturally to obtain pressureless sintered silicon carbide ceramics that are easy to process; S9 finishes the pressureless sintered silicon carbide ceramics to obtain the required product parts. During the processing, the pressureless sintered silicon carbide ceramics will not break or fall off.

[0026] Example 3 The formula of the pressureless sintered silicon carbide ceramic that is easy to process in this embodiment is shown in Table 1, and the preparation method includes the following steps: S1 Ingredient grinding: add water, binder, dispersant, plasticizer and lubricant into a stirred mill and grind for 1 hour, then add boron carbide powder, carbon fiber and carbon nanotubes and grind for 1 hour, finally add α-SiC ultrafine powder and β-SiC ultrafine powder and grind for 2 hours; S2. Screen the mud ground in step S1 using a 180-mesh screen to remove lumps in the mud; S3: pouring the slurry screened in step S2 into a mixing barrel, and starting granulation to obtain granular material; S4 sieve the granular material to 80 mesh to remove large particles to obtain homogenized granulated powder; S5: pouring the granulated powder into a mold for isostatic pressing at a molding pressure of 200 MPa to obtain a green body; S6: keeping the green body at 180°C for 6 hours for drying; S7 pre-processes the dried green body according to the designed shape and size; S8 The pre-processed green body is placed in a vacuum furnace and protected by a sagger for sintering: vacuum is drawn to 10 -2 Pa, heating to 600℃ at a rate of 40℃ / h and keeping it for 8h for degreasing, then introducing argon gas and heating to 2250℃ at a rate of 10℃ / h and keeping it for 1h, and cooling naturally to obtain pressureless sintered silicon carbide ceramics that are easy to process; S9 finishes the pressureless sintered silicon carbide ceramics to obtain the required product parts. During the processing, the pressureless sintered silicon carbide ceramics will not break or fall off.

[0027] Example 4 The formula of the pressureless sintered silicon carbide ceramic that is easy to process in this embodiment is shown in Table 1, and the preparation method includes the following steps: S1 Ingredient grinding: add water, binder, dispersant, plasticizer and lubricant into a stirred mill and grind for 1 hour, then add boron carbide powder, carbon fiber and carbon nanotubes and grind for 1 hour, finally add α-SiC ultrafine powder and β-SiC ultrafine powder and grind for 2 hours; S2. Screen the mud ground in step S1 using a 180-mesh screen to remove lumps in the mud; S3: pouring the slurry screened in step S2 into a mixing barrel, and starting granulation to obtain granular material; S4 sieve the granular material to 80 mesh to remove large particles to obtain homogenized granulated powder; S5: pouring the granulated powder into a mold for isostatic pressing at a molding pressure of 150 MPa to obtain a green body; S6: keeping the green body at 150°C for 8 hours for drying; S7 pre-processes the dried green body according to the designed shape and size; S8 The pre-processed green body is placed in a vacuum furnace and protected by a sagger for sintering: vacuum is drawn to 10 -2 Pa, heating to 700℃ at a rate of 30℃ / h and keeping it for 6h for degreasing, then introducing argon gas and heating to 2200℃ at a rate of 20℃ / h and keeping it for 3h, and cooling naturally to obtain pressureless sintered silicon carbide ceramics that are easy to process; S9 finishes the pressureless sintered silicon carbide ceramics to obtain the required product parts. During the processing, the pressureless sintered silicon carbide ceramics will not break or fall off.

[0028] Table 1 Formula of pressureless sintered silicon carbide ceramics for easy processing of Examples 1-4

[0029] Comparative Examples 1-7 The formulations of the pressureless sintered silicon carbide ceramics of Comparative Examples 1-7 are shown in Table 2, and the preparation methods are the same as those of Example 1.

[0030] Comparative Examples 8-14 The formulations of the pressureless sintered silicon carbide ceramics of Comparative Examples 8-14 are shown in Table 3, and the preparation methods are the same as those of Example 1.

[0031] Table 2 Formulas of pressureless sintered silicon carbide ceramics of Comparative Examples 1-7

[0032] Table 3 Formulas of pressureless sintered silicon carbide ceramics of Comparative Examples 8-14

[0033] The performance of the pressureless sintered silicon carbide ceramics prepared in Examples 1-4 and Comparative Examples 1-14 was tested, and the test results are shown in Tables 4-6. The apparent porosity and bulk density were tested in accordance with GB / T2997-2015 Test method for bulk density, apparent porosity and true porosity of dense shaped refractory products, and the fracture toughness was tested in accordance with GB / T 23806-2009 Test method for fracture toughness of precision ceramics - single edge precracked beam (SEPB) method.

[0034] Table 4 Performance test results of pressureless sintered silicon carbide ceramics prepared in Examples 1-4 that are easy to process

[0035] Table 5 Performance test results of pressureless sintered silicon carbide ceramics prepared in Comparative Examples 1-7

[0036] Table 6 Performance test results of pressureless sintered silicon carbide ceramics prepared in Comparative Examples 8-14

[0037] It can be seen from Table 4 that the pressureless sintered silicon carbide ceramics prepared in Examples 1-4 of the present invention, which are easy to process, have high sintering density, wherein the apparent porosity is ≤0.2% and the bulk density is ≥3.13 g / cm 3 , fracture toughness reaches 5.6-5.8MPa·m 1 / 2 , the edges and corners are not easily broken during the green processing and finishing process.

[0038] Compared with Example 1, in Comparative Example 1, an excessive amount of β-SiC ultrafine powder is added, the toughness of the green body is good, and the green body processing process does not cause edge and corner collapse; however, the excessive β-SiC ultrafine powder promotes the abnormal growth of SiC grains during the sintering process, reduces the strength of the material, hinders the discharge of pores, forms closed pores, reduces the density of the material, is not conducive to the fine processing of the product, and is prone to edge and corner collapse.

[0039] Compared with Example 1, too small a amount of water-soluble phenolic resin and plasticizer were added in Comparative Example 2, so that a sufficient network structure could not be formed inside the molded body, the strength of the green body was reduced, and the green body processing process caused edge and corner collapse, making the product unable to be pre-processed.

[0040] Compared with Example 1, excessive water-soluble phenolic resin and plasticizer are added in Comparative Example 3, which will cause the slurry to have excessive viscosity and uneven distribution of carbon in silicon carbide, resulting in local aggregation and growth of silicon carbide particles and pores. The unevenness will destroy the grain boundary bonding, cause microcracks and void defects, reduce the fracture toughness of the material, and cause edge and corner collapse during the processing process.

[0041] Compared with Example 1, too small a amount of carbon fiber and carbon nanotubes were added in Comparative Example 4, resulting in insufficient amount of toughening phase and uneven distribution around silicon carbide, making it difficult to form a continuous bridging network. The material after sintering could not achieve the expected toughening effect, and the processing process caused edge and corner collapse.

[0042] Compared with Example 1, excessive carbon fibers and carbon nanotubes are added in Comparative Example 5, which makes it difficult to disperse them evenly and easily forms local stress concentration points, which will significantly increase the microcracks and pore defects inside the material. These defects may become the preferred paths for crack propagation, thereby reducing the fracture toughness. Excessive addition of carbon fibers and carbon nanotubes may destroy the grain boundary structure, resulting in grain coarsening. Grain coarsening will reduce the grain boundary volume fraction, reduce the probability of crack deflection and bridging, and thus weaken the toughness.

[0043] Compared with Example 1, no boron carbide powder was added in Comparative Example 6, and the sintering process could not achieve the solid solution strengthening effect, the material could not be densified, and the density was insufficient; without the protective effect of boron carbide, the silicon carbide grains would overgrow, destroying the strength and toughness of the material, and causing edge and corner collapse during the finishing process.

[0044] Compared with Example 1, in Comparative Example 7, boron carbide powder is used instead of carbon fiber and carbon nanotubes. The product achieves a densification effect after sintering, but excessively increasing the strength cannot significantly achieve a toughening effect, and the processing process causes edge and corner chipping.

[0045] Compared with Example 1, the mutual replacement of polyvinyl alcohol and carboxymethyl cellulose or the imbalance in the ratio of the two in Comparative Examples 8-10 resulted in the failure to achieve a synergistic effect between the two and the failure to form a strong molecular network, which reduced the fluidity and plasticity of the granulated powder, reduced the strength of the green body after molding, and caused edge and corner collapse during the processing process.

[0046] Compared with Example 1, too much binder and plasticizer are added in Example 11, and the ratio of the two in Example 12 is unbalanced, which will lead to excessive viscosity of the mud and uneven distribution of carbon in silicon carbide, resulting in local aggregation and growth of silicon carbide particles and pores. The unevenness will destroy the grain boundary bonding, cause microcracks and void defects, reduce the fracture toughness of the material, and cause edge and corner collapse during the processing process.

[0047] Compared with Example 1, the use of water-soluble phenolic resin instead of polyvinyl alcohol and carboxymethyl cellulose in Comparative Example 13 will cause the viscosity of the mud to be too high and the fluidity to deteriorate, which is not conducive to the formation of a dense green body during molding, and the toughness of the green body will deteriorate. At the same time, the sintering temperature rising process cannot achieve the coordinated regulation of polyvinyl alcohol and carboxymethyl cellulose, and the pyrolysis temperature is too concentrated, resulting in local overheating and causing cracking of the green body.

[0048] Compared with Example 1, in Comparative Example 14, α-SiC ultrafine powder is used instead of β-SiC ultrafine powder, the activity of the material is not high, densification cannot be achieved, there is no volume effect of β-SiC ultrafine powder in high-temperature sintering, the fracture toughness of the material is reduced, and the material processing process causes edge and corner collapse.

[0049] In summary, the green body and finished product of the pressureless sintered silicon carbide ceramics that are easy to process and prepared by the present invention have high density and good toughness, which is beneficial to improving the precision and processing efficiency of the products.

Claims

1. Easy-to-process pressureless sintered silicon carbide ceramics, characterized in that: The invention comprises the following components in percentage by mass, wherein the total mass of the remaining components except the binder, dispersant, plasticizer, lubricant and water is calculated as 100%, and the binder, dispersant, plasticizer, lubricant and water are calculated as the percentage of the total mass of the remaining components: 91-95% of α-SiC ultrafine powder, 3-5% of β-SiC ultrafine powder, 0.5-1% of boron carbide powder, 0.5-2.5% of carbon fiber, 0.5-2.5% of carbon nanotube, 6-9% of binder, 0.5-1.5% of dispersant, 1-3% of plasticizer, 1-3% of lubricant and 100% of water; the total mass of the binder and the plasticizer is 7-10%, and the mass ratio of the binder to the plasticizer is 18:(2-9); wherein the binder is a water-soluble phenolic resin, and the plasticizer is polyvinyl alcohol and carboxymethyl cellulose in a mass ratio of 1:

1.

2. The pressureless sintered silicon carbide ceramic that is easy to process as claimed in claim 1, characterized in that: The purity of the α-SiC ultrafine powder is greater than 99.5wt.%, and the median diameter is 0.5-0.7μm.

3. The pressureless sintered silicon carbide ceramic that is easy to process as claimed in claim 1, characterized in that: The purity of the β-SiC ultrafine powder is greater than 99.5wt.%, and the median diameter is 0.1-0.2μm.

4. The pressureless sintered silicon carbide ceramic that is easy to process as claimed in claim 1, characterized in that: The purity of the boron carbide powder is greater than 99wt.%, with a median diameter of 0.5-1μm; the purity of the carbon fiber is greater than or equal to 98wt.%, with a diameter of 50-200nm and a length of 5-7μm; the purity of the carbon nanotube is greater than or equal to 98wt.%, with a diameter of 10-25nm and a length of 0.5-0.6μm.

5. The pressureless sintered silicon carbide ceramic that is easy to process as claimed in claim 1, characterized in that: The dispersant is ammonium polyacrylate.

6. The pressureless sintered silicon carbide ceramic that is easy to process as claimed in claim 1, characterized in that: The lubricant is oleic acid.

7. The method for preparing pressureless sintered silicon carbide ceramics that is easy to process as claimed in any one of claims 1 to 6, characterized in that: The steps include: S1 Ingredient grinding: add water, binder, dispersant, plasticizer, lubricant into a stirred mill for grinding, then add boron carbide powder, carbon fiber, carbon nanotubes for grinding, and finally add α-SiC ultrafine powder and β-SiC ultrafine powder for grinding; S2 uses a screen to screen the mud ground in step S1; S3 granulating the slurry screened in step S2 to obtain granular material; S4 sieving the granular material to obtain granulated powder; S5 isostatically pressing the granulated powder to obtain a green body; S6 drying the green body; S7 performs pre-processing on the green body after drying; S8 sintering the pre-processed green body to obtain pressureless sintered silicon carbide ceramics that are easy to process.

8. The method for preparing pressureless sintered silicon carbide ceramics that is easy to process as claimed in claim 7, characterized in that: In step S5, the isostatic pressing pressure is 150-200 MPa.

9. The method for preparing pressureless sintered silicon carbide ceramics that is easy to process as claimed in claim 7, characterized in that: In step S6, the drying temperature is 120-180° C. and the drying time is 6-12 hours.

10. The method for preparing pressureless sintered silicon carbide ceramics that is easy to process as claimed in claim 7, characterized in that: In step S8, the sintering process is as follows: at a vacuum degree of 10 -2 Pa, the temperature is raised from room temperature to 600-800°C at a rate of 20-40°C / h and kept for 4-8h, then argon is introduced to raise the temperature to 2100-2250°C at a rate of 10-30°C / h and kept for 1-3h, and the temperature is naturally lowered to obtain pressureless sintered silicon carbide ceramics that are easy to process.

Citation Information

Patent Citations

  • Pressureless sintering silicon carbide ceramic valve core and preparation process thereof

    CN102537510B

  • High-performance pressureless sintered silicon carbide bulletproof ceramic and preparation method thereof

    CN105198434A

  • Crucible structure for preparing silicon carbide single crystal, silicon carbide single crystal and preparation method and application of silicon carbide single crystal

    CN116084017A

  • Method for making ceramic matrix composite articles with progressive melt infiltration

    US20160175960A1